Ocorrência de parasitismo por Oestrus ovis em ovinos necropsiados da microrregião de Umuarama - Paraná, Brasil - Carvalho, Rafael Silveira; Ruivo, Maycon Araújo; Colli, Marcos Henrique Alcantara; Pereira, Valdomiro; Martinez, Antônio Campanha; Mazzucatto, Barbara Cristina; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Felippelli, Gustavo [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Soares, Vando Edésio [UNESP]; da Costa, Alvimar José [UNESP]; et al. (FapUNIFESP (SciELO), 2015)
Between January 2007 and September 2013, 71 sheep belonging to 12 farms in the Umuarama microregion, State of Paraná, were evaluated regarding presence of Oestrus ovis larvae, during necropsies. The farms from which these animals originated were visited and the owners and employees were interviewed. Occurrences of O. ovis parasitism in sheep were diagnosed for the first time on this microregion. Of the 71 animals, 12 (16.9%) were parasitized by O. ovis, with mean intensity of 2.25 larvae per infested head (1 to 8 larvae/infested head). There was a high correlation (0.81, p=0.0346) between the number of larvae and the macroscopic lesions observed in these animals’ nasal cavities, such that sheep with more than 3 larvae may contain mucupurulent secretions or epistaxis. From the interviews conducted, it was found that all the farm owners were applying chemical parasite control methods (helminths and/or O. ovis), administered to all animals in the herds every 30 days (91.6% of the producers), using derivatives of macrocyclic lactones and/or benzimidazoles/imidazothiazoles. Further studies need to be conducted in this particular region, in an attempt to elucidate the prevalence of O. ovis parasitism in herds.
Occurrences of Oestrus ovis parasitism in necropsied sheep in the Umuarama microregion, Paraná, Brazil
Keywords: Cavitary myiasis; Oestrus ovis; Sheep